2011
DOI: 10.1097/shk.0b013e3181f6aa44
|View full text |Cite
|
Sign up to set email alerts
|

Low Hemoglobin Levels During Normovolemia Are Associated With Electrocardiographic Changes in Pigs

Abstract: We studied whether low hemoglobin concentrations during normovolemia change the myocardial electrical current (electrocardiogram) in a pig model. Normovolemic anemia was achieved by stepwise replacing blood with colloids (hydroxyethyl starch 6%). We measured the length of the PQ-, QT-, QTc, and the ST interval as well as the amplitude of the Q wave and T wave at hemoglobin concentrations of 9.5, 8.0, 5.5, 3.8, and 3.3 g·dL. Normovolemic anemia is accompanied by a gradual prolongation of the QT and QTc interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In a study of 30 non-pregnant females with severe iron deficiency anemia, Vitthal HK et al showed that the QTc interval was shorter in patients than in the control group and there was a significant positive correlation between serum ferritin level and the QTc interval [10]. In another study of non-pregnant females with severe iron deficiency anemia, positive correlations were also reported between serum ferritin or hemoglobin and QTc (12). The results of the current study were consistent with the literature in this respect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 30 non-pregnant females with severe iron deficiency anemia, Vitthal HK et al showed that the QTc interval was shorter in patients than in the control group and there was a significant positive correlation between serum ferritin level and the QTc interval [10]. In another study of non-pregnant females with severe iron deficiency anemia, positive correlations were also reported between serum ferritin or hemoglobin and QTc (12). The results of the current study were consistent with the literature in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Several electrocardiographic changes have been identified in patients with anemia, including ST segment depression, Twave inversion, extension or shortening of the QT interval, and reduced QRS complex amplitude [10,12,13]. The increase in sympathetic excessive activity from the shortened QT interval with hypoxia and reduced myocardial oxygen source can be possibly held responsible for the pathophysiological connection between anemia and prolonged QT intervals [10,13].…”
Section: Discussionmentioning
confidence: 99%
“…However, in another experimental study, hemoglobin levels of 4-5 g/dL were associated with changes in heart rate variability (HRV), obtained by time-and frequency-domain analysis of ECG data, but ST-segment changes were not observed until a mean hemoglobin level of 3 g/dL, at which point oxygen consumption also decreased . Other ECG changes not related to the ST-segment were observed in another experimental study by the same group, in which ANH induced gradual prolongation of the QT and QTc interval and reduction in the amplitude of the T wave (Scheller et al, 2011). In both studies, early ECG alterations were observed in the absence of traditional transfusion triggers, such as increase in serum lactate levels, elevation of the ST-segment or arrhythmias.…”
Section: Heart Tolerance To Acute Anemiamentioning
confidence: 63%
“…However, in another experimental study, hemoglobin levels of 4-5 g/dL were associated with changes in heart rate variability (HRV), obtained by time-and frequency-domain analysis of ECG data, but ST-segment changes were not observed until a mean hemoglobin level of 3 g/dL, at which point oxygen consumption also decreased (Lauscher et al, 2011) . Other ECG changes not related to the ST-segment were observed in another experimental study by the same group, in which ANH induced gradual prolongation of the QT and QTc interval and reduction in the amplitude of the T wave (Scheller et al, 2011). In both studies, early ECG alterations were observed in the absence of traditional transfusion triggers, such as increase in serum lactate levels, elevation of the ST-segment or arrhythmias.…”
Section: Heart Tolerance To Acute Anemiamentioning
confidence: 72%